PERJANJIAN BOT (BUILD OPERATE AND TRANSFER) ANTARA PT. SEAWORLD INDONESIA DENGAN PT PEMBANGUNAN JAYA ANCOL Tbk - Chandra Adcha Mita, Arasina; Heniyatun, Heniyatun (Varia Justicia, 2015)
Cooperation Cooperation BOT build operate and transfer (BOT) is a form of cooperation agreements carried out between holders of land rights to the investor which holders of land rights would entitle the investor to erect a building for the duration of the agreement to transfer ownership of the building to holders of land rights after a period ofwake up in order to deliver an end. One form of the agreement made by PT. Jaya Ancol construction with vehicle manager of Sea World for 20 years ended 20 September 2014. This thesis entitled "Agreement Bot (Build Operate And Transfer) between PT.Seaworld Indonesia with PT Building Jaya Ancol Tbk ". The purpose of this study was to determine the problems that arise in the implementation of BOT agreement between PT. Sea Wold Indonesia with PT. Jaya Ancol Tbk development and how its completion. The research method using normative juridical approach. Materials research using primary and secondary data, specifications research using descriptive analytical research, libraries and research tools using interviews, interview techniques and research data analysis method by means of qualitative methods. Based on the research that the differences in perception by each of the parties to cause problems in the BOT agreement. PT. Jaya Ancol development assume that the clause 8 subsection 5 of the Agreement between PT. Development Jaya Ancol Tbk and Sea World considers that the current agreement expires, PT. Sea World Indonesia handing back land and building project to PT. Jaya Ancol Tbk development, including supporting infrastructure and its management rights. The guidelines are used as Sea World Indonesia is clause 8 subsection  6 which states PT. Sea World Indonesia, have a perception extend the management for a maximum of 20 years, and shall notify in writing the Jaya Ancol no later than one year agreement period expires. PT. Sea World is obliged to hand over the building and its assets to PT. Development Jaya Ancol Tbk because the agreement has expired according to the agreement specified in the agreement. The decision of Supreme Court of Supreme Court (MA) concerning a dispute between PT. Development Jaya Ancol Tbk and PT. Sea World Indonesia resulted in the decision that the Supreme Court granted the petition of the Petitioners stating that the extension does not apply immediately or automatic but conditional can be extended with a new agreement that was agreed Petitioner and Respondent Convention Convention.  Respondent punish the Convention to submit the building, including equipment, facilities and other inventory items.